Vida e trabalho: um estudo sobre mulheres extrativistas de mangaba na Ilha do Marajó, Estado do Pará - LIMA, Bianca Ferreira (Universidade Federal do Pará, 2021)
This study dedicates itself to the role women develop in the mangaba extraction in the northern region of Brazil. In this regard, the main objective of the present Master’s thesis is to identify and characterize the mangaba extraction by analyzing the women’s role in the activity. The case study was developed in Vila Paca, a small village in Marajó island, Pará. The methodology was structured by qualitative approaches focused on the following procedures: observation, meetings and interviews (semi-structured and questionnaires) with the women involved in mangaba extraction who live in Vila Paca and their domestic groups, as well as some persons from adjacent places who also work with mangaba. Two aspects where subject to the analysis: a) the role that women extractors play in their domestic groups; b) The importance of mangaba extraction in the midst of the other activities. The main results show that: i) the magaba extraction is a seasonal activity conducted exclusively by women, with the help of their children; ii) There are also four other places developing the mangaba extraction in that region, and there are variations in administration, access and management of the magaba trees, between them; iii)There’s no Government programs, technical aid, financial incentives or consultancy towards the native fruits extraction throughout the stages (from gathering to marketing); iv) the activity, as performed by this group of women, ensures the conservation of the local natural resources; v)the main share of the mangaba’s productive chain occurs in a domestic space (processing and sale), which favors the condition of social invisibility of those women through their jobs. The main conclusions shows that in that region the extraction activity is “naturalized”, and that in any stage of the work (gathering, processing, or marketing) it receives the status of work, however this don’t means the activity itself doesn’t have meaning in the eyes of the domestic groups and other actors but is relegated to second rank status when it comes to the jobs considered productive among them.